REVIEW LITERATUR: PENGARUH AKTIVITAS KEBUGARAN JASMANI TERHADAP PERKEMBANGAN MOTORIK DAN KESEHATAN FISIK PESERTA DIDIK (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the influence of physical fitness activities on students’ motor development and physical health through a literature review approach. The analysis was conducted using ten national journal articles published between 2022 and 2025. The findings indicate that physical fitness activities significantly improve fundamental motor abilities such as strength, agility, balance, coordination, and reaction speed. Fitness activities also contribute to the development of fine motor skills that support students’ academic performance. In terms of physical health, fitness exercises enhance cardiorespiratory capacity, flexibility, core muscle strength, body metabolism, and reduce the risk of obesity. These findings highlight that physical fitness activities are essential components in the educational process and should be applied in a structured manner to support students’ optimal growth and development.